Electrotechnological complex of plants energy-efficient irradiation in greenhouses - Chervinsky, L.; Makoda, O. (Energy and Automation, 2025)
The electrotechnological complex of energy-efficient irradiation of plants in greenhouses is an important aspect in modern agro-industrial production, as it provides optimal conditions for plant growth and development, reducing energy consumption. This complex uses modern lighting technologies that allow for the effective use of natural and artificial lighting, optimizing its intensity and spectrum to ensure maximum photosynthetic effect. One of the main principles of energy-efficient irradiation is the use of light-emitting diode (LED) lamps, which makes it possible to regulate the light spectrum, adapting it to the specific needs of plants. These lamps have high energy efficiency and a long service life, which allows reducing electricity and maintenance costs. In addition, the use of automated control systems, such as light and temperature sensors, allows maintaining an optimal microclimate in greenhouses. Integration of such systems into agro-industrial complexes allows not only to increase yields, but also to reduce the impact on the environment due to the rational use of energy. The development and implementation of energy-efficient irradiation technologies in greenhouses is an important step towards the sustainable development of the agricultural sector, in particular in the context of climate change and increasing demand for environmentally friendly products. Key words: electro-technological complex, energy efficiency, plant irradiation, greenhouse, LED lighting, automation, agro-industrial production